Coordinating Service Compositions : Model and Infrastructure for Collaborative Creation of Electronic Documents - Schuster, Nelly (KIT Scientific Publishing, 2013)
Electronic documents frequently include contributions from different human and non-human sources. The Web, for instance, offers ever-changing content and services which can perform activities during document creation. This thesis introduces a solution for collaborative document creation which maps contributions of human and non-human participants to software services. The joint flexible composition and coordination of these services leads to a novel understanding of dynamic Web-based documents.
English
Keywords: flexibility; collaboration; RESTful Web services; service composition; coordination